Engaging Physician Learners Through a Web-Based Platform: Individualized End-of-Life Education. (September 2016) - Bergman, Jonathan; Ballon-Landa, Eric; Lerman, Steven E.; Kwan, Lorna; Bennett, Carol J.; Litwin, Mark S.
Background: Web-based modules provide a convenient and low-cost education platform, yet should be carefully designed to ensure that learners are actively engaged. In order to improve attitudes and knowledge in end-of-life (EOL) care, we developed a web-based educational module that employed hyperlinks to allow users access to auxiliary resources: clinical guidelines and seminal research papers. Methods: Participants took pre-test evaluations of attitudes and knowledge regarding EOL care prior to accessing the educational module, and a post-test evaluation following the module intervention. We recorded the type of hyperlinks (guideline or paper) accessed by learners, and stratified participants into groups based on link type accessed (none, either, or both). We used demographic and educational data to develop a multivariate mixed-effects regression analysis to develop adjusted predictions of attitudes and knowledge. Results: 114 individuals participated. The majority had some professional exposure to EOL care (prior instruction 62%; EOL referral 53%; EOL discussion 56%), though most had no family (68%) or personal experience (51%). On bivariate analysis, non-partnered ( p = .04), medical student training level ( p = .03), prior palliative care referral ( p = .02), having a family member ( p = .02) and personal experience of EOL care ( p < .01) were all associated with linking to auxiliary resources via hyperlinks. When adjusting for confounders, β coefficient estimates and least squares estimation demonstrated that participants clicking on both hyperlink types were more likely to score higher on all knowledge and attitude items, and demonstrate increased score improvements. Conclusion: Auxiliary resources accessible by hyperlink are an effective adjunct to web-based learning in end-of-life care.